If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+34+10x-23=x
We move all terms to the left:
7x+34+10x-23-(x)=0
We add all the numbers together, and all the variables
16x+11=0
We move all terms containing x to the left, all other terms to the right
16x=-11
x=-11/16
x=-11/16
| 4k-18-8k=18-k | | s/4-1=4 | | 5y-9=2-5y | | -6(h-4)=-24 | | 12+19u=7u-18+14u | | (4x+5)=3(x+5) | | 13+7=8x+27 | | 4c-22=34 | | 4(3x5)=6x-2 | | 3=j/3-4 | | -6|h-4|=-24 | | 10+3r=16 | | -7d-3=10d-6 | | 5(y-94)=15 | | 5x-17=-2x^ | | 7(1d-2)-3d=5-2(d+3)+4d | | 5(y−94)=15 | | -11+-2=-20-10t | | 5x-17=-2x | | v/4+11=18 | | 10z+20=60 | | 6x+3+2x=-13 | | 3(2x+3)-2=(X-2) | | 1/2(6b-8)=1b | | 1/y-4+2/y+3=10/y^2-y-12 | | 6(b-88)=12 | | 14+2x=-6-3x. | | -24.26674+0.6a=3.6a-0.28a | | x/4=x-9/3 | | p/4+10=11 | | 13+16+18j=19j+10 | | 6^-2m=216 |